Development of chloroplast transformation and gene expression regulation technology in land plants - An, Yaqi; Wang, Yue; Wang, Xinwei; Xiao, Jianwei (Frontiers in Plant Science, 2022)
Chloroplasts in land plants have their own small circular DNA that is presumed to have originated from cyanobacteria-related endosymbionts, and the chloroplast genome is an attractive target to improve photosynthetic ability and crop yield. However, to date, most transgenic or genetic engineering technologies for plants are restricted to manipulations of the nuclear genome. In this review, we provide a comprehensive overview of chloroplast genetic engineering and regulation of gene expression from the perspective of history and biology, focusing on current and latest methods. In addition, we suggest techniques that may regulate the chloroplast gene expression at the transcriptional or post-transcriptional levels.